Implementing patient-centred outcome measures in palliative care clinical practice for adults (IMPCOM): protocol for an update systematic review of facilitators and barriers - Antunes, B; Barclay, S; Kuhn, I; Eagar, K; Bausewein, C; Murtagh, F; Etkind, S; Bowers, B; Dixon, S; Lovick, R; Harding, R; Higginson, I; et al. (F1000Research, 2023)
Background: Despite the development of patient-centred or patient-reported outcome measures (PCOMs or PROMs) in palliative and end-of-life care over recent years, their routine use in practice faces continuing challenges. Objective: To update a highly cited literature review, identify and synthesise new evidence on facilitators, barriers, lessons learned, PCOMs used, models of implementation, implementation outcomes, costs, and consequences of implementing PCOMs in palliative care clinical practice. Methods: We will search MEDLINE, PsycINFO, CINAHL, Embase, Emcare, SCI-Expanded, SSCI, ESCI, and BNI. The database search will be supplemented by a list of studies from the expert advisory committee, hand-searching of reference lists for included articles, and citations of the original review. We will include primary studies using a PCOM during clinical care of adult patients with advanced disease in palliative care settings and extract data on reported models of implementation, PCOMs, facilitators, barriers, lessons learned, costs, and implementation outcomes. Gough’s Weight of Evidence Framework will be used to assess the robustness and relevance of the studies. We will narratively synthesise and tabulate the findings. This review will follow PRISMA, PRISMA-Abstract, PRISMA-P, and PRISMA-Search as the reporting guidelines. Source of funding: Marie Curie. The funder is not involved in designing or conducting this study. Protocol registration: CRD42023398653 (13/02/2023)